2002
DOI: 10.1165/rcmb.4746
|View full text |Cite
|
Sign up to set email alerts
|

Altered Phospholipid Composition and Aggregate Structure of Lung Surfactant Is Associated with Impaired Lung Function in Young Children with Respiratory Infections

Abstract: Alterations to pulmonary surfactant structure, composition, and function contribute to the severity of respiratory infections. Analysis of bronchoalveolar lavage fluid (BALF) from children undergoing diagnostic bronchoscopy for structural abnormalities (control group, n = 24), asthma (n = 18), lung infection (n = 30), and cystic fibrosis (CF, n = 15) showed that BALF phospholipid concentration decreased with age for the control group and was elevated in all disease groups. The fractional concentration of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 28 publications
4
45
2
Order By: Relevance
“…The high percentage of phospholipid in secreted material was in agreement with other studies of secretion from lungs in vivo (3) and with recent studies with adult type II alveolar epithelial cells in vitro (19,20). The ratios of SP-A and SP-B to phospholipid secreted from these cells were similar to those in tracheal aspirate samples from premature infants.…”
Section: Characterization Of Fetal Alveolar Epithelial Cells Differensupporting
confidence: 90%
“…The high percentage of phospholipid in secreted material was in agreement with other studies of secretion from lungs in vivo (3) and with recent studies with adult type II alveolar epithelial cells in vitro (19,20). The ratios of SP-A and SP-B to phospholipid secreted from these cells were similar to those in tracheal aspirate samples from premature infants.…”
Section: Characterization Of Fetal Alveolar Epithelial Cells Differensupporting
confidence: 90%
“…In contrast to the situation in severely injured lungs, the relatively mild lung injury observed in these spontaneously breathing septic animals was associated with no changes in LA pool sizes but a decrease in SA. This resulted in an increased percentage of LA in these spontaneously breathing animals, a finding also reported in a human study evaluating spontaneously breathing children with respiratory infections [12]. The current authors speculate that these changes in the endogenous surfactant system represent a compensatory response of the host to the initial insult.…”
Section: Discussionsupporting
confidence: 82%
“…Although earlier interventions would seem appropriate, a better understanding of surfactant alterations at this stage of the disease is required to justify this approach. Recent studies have shown that changes in the alveolar surfactant subfractions occur in animals and humans with less severe lung injury, while spontaneously breathing [10][11][12].…”
mentioning
confidence: 99%
“…Recently, elevated minimum surface tension values were found in surfactant isolated from children with cystic fibrosis and with pneumonia; surfactant proteins were not examined in that study (33). Adults with acute respiratory distress syndrome have low concentrations of SP-A and SP-B both before and during their lung disease, and minimum surface tension is elevated (30,44,45).…”
mentioning
confidence: 93%
“…None of the observed changes in phospholipid composition is likely to affect surfactant function, particularly in view of unchanged phosphatidylcholine content. The concentration of saturated phosphatidylcholine in surfactant is reduced in both pneumonia and adult acute respiratory distress syndrome (20,33). Because of the limited amount of surfactant pellet from each TA collection, we performed the measurements of phospholipid composition on pooled residual samples and were not able to assess either saturated phosphatidylcholine or molecular species of phosphatidylcholine.…”
mentioning
confidence: 99%